O‘ZBЕK TILSHUNОSLIGIDА NАMАNGАN SHEVАLАRI - Musurmоn Usmоnоv (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The article presents views on the history and level of study of the dialects of the Namangan region. The views and comments of scientists who studied dialect are described.